Analysis of Sushi Rice: Preparation Techniques, Physicochemical Properties and Quality Attributes - Wondyfraw Tadele Wonbebo; Piotr Kulawik; Andrzej Szymkowiak; Eskindir Endalew Tadesse (Applied Sciences)
This study explores the multifaceted aspects of sushi rice preparation, including the washing, soaking, and cooking processes and their impact on the texture, microbial, colour, and sensory properties of rice. Selenio rice, a premium short-grain rice of the Japonica variety, was analyzed for variations in amylose content and viscosity profiles. The study highlights how the rice’s compositional characteristics, particularly the amylose-to-amylopectin ratio, influence gelatinisation and cooling behaviour. The study examined washing duration, water-to-rice ratios, soaking times, and seasoning effects on product quality. The results demonstrated that washing rice for 230 s was optimal for the nigiri-forming process, while extending soaking beyond 3 min provided no additional water absorption benefits. Water temperature during soaking (10–50 °C) had minimal impact on water absorption. The addition of a vinegar mix reduced the pH to below 4.5, improving shelf life and sensory properties. During storage, textural profile analysis revealed that hardness and chewiness increased while adhesiveness decreased across all samples, with lower water-to-rice ratios resulting in firmer rice that maintained structural integrity better during storage. Sensory evaluation showed declining scores for odour, taste, texture, and overall acceptability over the 10-day storage period, though colour and appearance were less affected. Microbial loads remained relatively low across all samples during storage, and rice colour showed minimal changes over time. These findings contribute significantly to optimizing sushi rice production processes, ensuring consistent quality and desirable textural attributes throughout storage while advancing the broader fields of rice research and culinary science.